IN-PRISON ARTISTIC WORKSHOPS WITH TEENAGERS AND ADULTS: SUBJECTIVITY IN DISPUTE - Marcela Gaete Vergara (Universidad Nacional del Nordeste, 2022)
The following article develops some of the findings carried out on qualitative research carried out from 2018 to 2020. Its objective was to map educative and socio-educative school projects that were implemented at prison centers from Metropolitan region, Chile. During the first stage, schools and institutions were identified as well as foundations, organizations, and collectives with a non-formal system of education. Thus, educators from 68 institutions out of 78 were interviewed to finally generate focus groups and discussions. In this scenario, artistic education is completely diminished, mostly in institutions advocated to teenagers, in comparison to work training and school opportunities in primary and secondary levels. Artistic workshops have been managed almost uniquely by these same prison centers as a way to intervene people based on the social reintegration logic. Nevertheless, the 10 monitors in charge of artistic workshops inside prison are disputing this logic that considers art as a reintegration tool. On the contrary, they understand artistic formative processes as a politic tool, to configure and reconfigure people's modes of self-sensing, self-dominating, reflecting, and thinking in connection to the surrounding world from which emerges other subjective modes which have been denied to those in and out prison as a consequence of a life of neglect and symbolic and material imprisonment.